(untitled) (Portuguese Journal of Family Medicine and General Practice, 2003)
At present, it may be inappropriate and ethically reprehensible discourage or do not offer the possibility of screening men who request and ask for a screening test for prostate cancer without prior information accurate, unbiased and up to date.